The Practice of the Community Pharmacists in Managing Potential Drug-Drug Interactions: A Simulated Patient Visits - Hamadouk RM; Albashair ED; Mohammed FM; Yousef BA (Dove Medical Press, 2022)
Riham M Hamadouk,1 Esra D Albashair,1 Fatimah M Mohammed,1 Bashir A Yousef2 1Department of Clinical Pharmacy, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 2Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Khartoum, SudanCorrespondence: Bashir A Yousef, Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Al-Qasr Ave, Khartoum, 11111, Sudan, Tel +249155662037, Fax +249183780696, Email bashiralsiddiq@gmail.comBackground: Drug-drug interactions (DDIs) can cause treatment failure and serious adverse drug reactions, leading to morbidity and mortality. Due to their significant effects on the patient's health, community pharmacists (CPs) competence in detecting and preventing these interactions is essential to provide optimal health services. Thus, this study aimed to explore the performance of the CPs in situations involving the presence of potential DDIs.Methods: A cross-sectional, simulated patient study was conducted in 235 community pharmacies in the Khartoum locality. Two scenarios were used to evaluate the performance of the CPs. Ten final year B. Pharm. students were selected to act as simulated patients (SPs); they were trained for two weeks to familiarize their roles. All encounters were documented immediately after leaving the pharmacy by the SPs in the data collection form.Results: All planned SPs visits were completed, resulting in 470 visits. None of the CPs asked about the patients' medication history in both scenarios. After the SPs provided information about the drug used currently by the patient, 13.6% and 23.4% of the CPs had identified the potential DDIs in scenario 1 and scenario 2, respectively. In scenario 1, 59.4% distinguished the interaction of simvastatin with both drugs, while, in scenario 2, 74.5% recognized the interaction of warfarin with both drugs. In identifying DDIs, around half of the CPs were dependent on their knowledge or using drug interaction checker programs. The most common intervention made by the CPs was referring the patient to the prescriber (56.3% CPs in scenario 1 and 60% CPs in scenario 2).Conclusion: CPs practice in identifying and managing potential DDIs was poor. The current CPs practices need substantial improvement. Therefore, professional education and the use of software programs in community pharmacies should be encouraged.Keywords: drug-drug interactions, simulated patient, community pharmacist, medication history